2008
DOI: 10.1080/0972060x.2008.10643618
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Nitrogen and Potassium Fertilizer on Growth and Essential Oil Content ofCymbopogon citratusandVetiveria zizanioides

Abstract: To study the effects of nitrogen and potassium fertilizers, a field experiment was conducted in watershed area of Kulhal, DehraDun at 20 % slope. Experiment consisted of four doses (0, 25, 50 and 75 Kg ha -1 ) of nitrogen and potassium and sixteen possible combinations were laid out in Randomized Block Design in two replications. Observations recorded after two years of plantation revealed that height, total biomass production and essential oil content was maximum in Lemon grass under the treatment of 50 Kg ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The treatment of 200kg/ha of N resulted in the highest yield values, EO (%), p-cymene, limonene, dihydrotagetone, E-tagetone, Z-tagetone, Z-ocimenone, and E-ocimenone of Tagetes minuta (Omidbaigi et al, 2008b). The greatest biomass and EO composition of lemon grass herb were detected at a rate of 50kg (N)/hectare (Rashmi & Singh, 2008). Davana plants exposed to 94kg (N)/ha have enhanced growth and higher yields and EOs than those of the untreated control (Kumar et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…The treatment of 200kg/ha of N resulted in the highest yield values, EO (%), p-cymene, limonene, dihydrotagetone, E-tagetone, Z-tagetone, Z-ocimenone, and E-ocimenone of Tagetes minuta (Omidbaigi et al, 2008b). The greatest biomass and EO composition of lemon grass herb were detected at a rate of 50kg (N)/hectare (Rashmi & Singh, 2008). Davana plants exposed to 94kg (N)/ha have enhanced growth and higher yields and EOs than those of the untreated control (Kumar et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…N affects EO metabolisms and their production through carbon assimilation and acetyl‐CoA formation via mevalonate pathway 27 . The EO has improved for many plants due to the presence of N; thyme, black cumin, coriander, anise, hyssop, davana, dill, Tagetes minuta , piper, sweet fennel, lemon grass and parsley EOs and their major constituents were significantly improved in response to N 28–38 . Some past researches have indicated that S has a positive effect on the yield and composition of basil and wild marigold EOs 23,39,40 …”
Section: Discussionmentioning
confidence: 99%
“…25,26 N affects EO metabolisms and their production through carbon assimilation and acetyl-CoA formation via mevalonate pathway. 27 The EO has improved for many plants due to the presence of N; thyme, black cumin, coriander, anise, hyssop, davana, dill, Tagetes minuta, piper, sweet fennel, lemon grass and parsley EOs and their major constituents were significantly improved in response to N. [28][29][30][31][32][33][34][35][36][37][38] Some past researches have indicated that S has a positive effect on the yield and composition of basil and wild marigold EOs. 23,39,40 Application of VIT (such as α-TCP) leads to an increase in the cellulose, cellulose/lignin content and a deficiency in lignin; this, in turn, leads to an increase in photosynthesis by increasing the activity of photosensitive enzymes, 41 which involved mevalonic acid pathway.…”
Section: Effect Of Gsh α-Tcp and Their Interactions On The Eo Constit...mentioning
confidence: 99%
“…This is thought to be because the nutrients needed by plants are not yet available, considering the slow nature of compost. Based on research results [11] When 75 kg/ha of potassium was applied, the percentage of essential oil dropped to 0.63%, The highest percentage of essential oil (0.72%) was found in plants that were given 25 kg of nitrogen and 50 kg of potassium per hectare. So there is no real difference between plants given compost and those not given compost.…”
Section: Root Crown Ratiomentioning
confidence: 99%